Upaya Membangun Komunitas yang Peduli Lingkungan melalui Kegiatan Gotong Royong Menjaga Kebersihan Musholla - Amirul Shidiq; Amir Bandar Abdul Majid; Didit Darmawan; Mochamad Saleh; Wakid Evendi; Moh. Syaiful Anwar; Muhammad Bangsu (Manfaat : Jurnal Pengabdian Pada Masyarakat Indonesia, 2024)
This community service research aims to describe hygiene care activities with the community located in the Al-Musta'in Mushollah, Ngentak Hamlet, Sumberjo Village, Plandaan District, Jombang Regency. The author used descriptive qualitative research with observation and documentation data collection techniques at the research location. The research method used before the activity was Particaptory Action Research (PAR). The results of the research show that the residents of Sumberjo Village have a high level of concern for cleanliness around the Al-Musta'in Musholla area in Ngentak Hamlet. These findings illustrate that there is a high sense of togetherness and solidarity among residents, as well as showing the existence of strong values of friendship and mutual respect between fellow residents. This reflects the culture of mutual cooperation that is still strong in society, where they not only care about the cleanliness of the environment individually, but also actively participate in maintaining cleanliness together, making the Al-Musta'in Musholla a focal point for uniting in efforts environmental maintenance and positive social values.